Pencegahan tindak kekerasan dalam rumah tangga dengan assertive training theraphy: Sebuah studi literatur - Himamie, Rushoyfah; Ardani, Tristiadi Ardi (Maliki Interdisciplinary Journal, 2024)
Violence in household is one of the cases that often occurs in Indonesia. Victims of household violence require special treatment due to the violence they have experienced. However, to reduce the number of household violence cases, preventive measures are also needed as an effort to eliminate domestic violence. This article aims to provide alternative prevention for individuals who are at risk of becoming perpetrators of household violence. This research uses the library research method with references in the form of scientific articles. The result of this research conclude that providing assertive training can prevent someone from committing violence, especially violence in household